International Framework Agreements and the Future of Collective Bargaining in Multinational Companies - Bourque, Reynald (Just Labour, 2008)
This article emphasizes the contribution of International Framework Agreements (IFAs) to collective bargaining within multinational companies (MNC). For this purpose, we used various data, including content analysis of 42 IFAs and interviews with representatives of the five Global Union Federations (GUFs) involved in the negotiation of these IFAs, in order to assess the content and efficiency of these agreements. Our analysis reveals that IFAs usually include a commitment by the signatory MNC to conform to ILO’s core conventions in all its operations, and to inform its business partners of their obligations under the agreement. Regular meetings are held with unions’ representatives for the monitoring of thes e agreements to ensure their respect by the signatory multinational companies and their business partners. According to GUFs’ representatives, the IFAs have been effective in protecting basic trade union rights covered by ILO conventions 87 and 98. In the last part, we emphasize the IFAs’ contribution to collective bargaining within MNCs and discuss the prospects for future development of international collective bargaining, particularly in light of Levinson’s seminal work (1972) on this subject.